Prevalence and determinants of meeting minimum dietary diversity among children aged 6–23 months in three sub-Saharan African Countries: The Demographic and Health Surveys, 2019–2020 - Ba, Djibril M.; Ssentongo, Paddy; Gao, Xiang; Chinchilli, Vernon M.; Richie, John P.; Maiga, Mamoudou; Muscat, Joshua E. (Frontiers in Public Health, 2022)
Background: Dietary diversity is an indicator of nutritional adequacy, which plays a significant role in child growth and development. Lack of adequate nutrition is associated with suboptimal brain development, lower school performance, and increased risk of mortality and chronic diseases. We aimed to determine the prevalence and determinants of meeting minimum dietary diversity (MDD), defined as consuming at least five out of eight basic food groups in the previous 24-hours in three sub-Saharan African countries. Methods: A weighted population-based cross-sectional study was conducted using the most recent Demographic and Health Surveys (DHS). MDD data were available between 2019 and 2020 for three sub-Saharan African countries (Gambia, Liberia, Rwanda). The study population included 5,832 children aged 6-23 months. A multivariable logistic regression model was developed to identify independent factors associated with meeting MDD. Results: Overall, the weighted prevalence of children who met the MDD was 23.2% (95% CI: 21.7%-24.8%), ranging from 8.6% in Liberia to 34.4% in Rwanda. Independent factors associated with meeting MDD were: age of the child adjusted odds ratio (aOR)=1.96, 95% CI: 1.61, 2.39 for 12-17 months vs. 6-11 months), mothers from highest households’ wealth status (aOR= 1.86, 95% CI: 1.45-2.39) compared with lowest, and mothers with secondary/higher education (aOR= 1.69, 95% CI: 1.35-2.12) compared with those with no education. Mothers who were employed, had access to a radio, and those who visited a healthcare facility in the last 12 months were more likely to meet the MDD. There was no significant association between the child’s sex and the odds of fulfilling the MDD. Conclusion: There is substantial heterogeneity in the prevalence of MDD in these three sub-Saharan African countries. Lack of food availability or affordability may play a significant role in the low prevalence of MDD. Mothers’ education, employment, households’ wealth status, and access to a radio were some of the factors significantly associated with MDD. Nutritional education programs targeting mothers are needed to increase the uptake of MDD in sub-Saharan Africa and prevent undernutrition.